Islamic Legislation: Sources and Provisions - Amir Abdullah Khalid Al-Sharif; Nazim Ali Khader; Al_Sayed Abdulaziz Mortuda (International Journal of Law Research and Studies, 2024)
Legislation is derived from Sharia, which is the clear approach and path. Legislation means establishing the systems and rules that Allah Almighty has determined for Muslims to regulate their lives in terms of worship, transactions, and relationships. Islamic legislation includes all aspects of economic, political, and social life, the judicial system and penalties, and other rules that regulate people’s lives and interactions. Islamic legislation has gone through several stages since the beginning of the call of the Prophet Muhammad, peace and blessings be upon him, namely: the era of prophecy, the era of the Rightly Guided Caliphs, the era of the Followers, the era of the Followers of the Followers, the era of imitation, and the current era. Sharia includes the rulings that Allah Almighty revealed to His Messenger Muhammad, peace and blessings be upon him, in the Holy Quran or the Sunnah of the Prophet, and it is based on revelation. The rulings that Islamic law brought are divided into three main sections: doctrinal rulings, moral rulings, and practical rulings (jurisprudence).